2023
DOI: 10.1145/3611022
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Homebrewed Hybridity: Designing Hybrid Digital Boardgames for Distanced Play

Lucy A. Sparrow,
Melissa J. Rogerson

Abstract: In 2020–2021, under the restrictions associated with the COVID-19 pandemic, boardgame players around the world sought out ways to play physical boardgames with each other despite being physically apart. Their creative appropriations of digital technologies and physical tools to allow for hybrid distanced play demonstrate not only the resilience of boardgaming as a hobby, but also provide important insights into the design of novel distanced hybrid digital boardgames (DHDBs). Through a survey of over 1300 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Such approaches were also used by other board game players. In their study on homebrewed hybridity during COVID-19 times, Sparrow and Rogerson [85] found that distanced boardgame players used at-home fabrication devices such as printers and 3D printers.…”
Section: Craft and Fabrication Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such approaches were also used by other board game players. In their study on homebrewed hybridity during COVID-19 times, Sparrow and Rogerson [85] found that distanced boardgame players used at-home fabrication devices such as printers and 3D printers.…”
Section: Craft and Fabrication Gamesmentioning
confidence: 99%
“…This enables digital game logic to have effects on tangible components (digital −→ physical), but also allows the game to enact players' motion commands (as done in DungeonMaker), or acquire and react to player-initiated state changes on the board (physical −→ digital). In turn, this may enable tangible remote play [56][57][58]85], as demonstrated by commercial projects like Phantom Chess 13 . Creation + Destruction.…”
Section: Emergent Design Elements Beyond Dungeonmakermentioning
confidence: 99%